2021
DOI: 10.1128/spectrum.00213-21
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Aspergillus oryzae Mycelium Growth and Conidium Production by Irradiation with Light at Different Wavelengths and Intensities

Abstract: Aspergillus oryzae is a safe filamentous fungus widely used in the food, medicine, and feed industries, but there is currently not enough research on the light response of A. oryzae . In this study, 12 different light conditions were set and A. oryzae GDMCC 3.31 was continuously irradiated for 72 h to investigate the effect of light on mycelial growth and conidium production. Specifically, each light condition was the combination of one light waveleng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…CBL, whose intensity is higher than the threshold, significantly inhibited A. oryzae GDMCC 3.31. The threshold of blue light intensity for mycelium development and conidia generation were respectively 60 and 40 µmol•m −2 •s −1 [11]. Similar light responses have been reported in other A. oryzae strains [12].…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…CBL, whose intensity is higher than the threshold, significantly inhibited A. oryzae GDMCC 3.31. The threshold of blue light intensity for mycelium development and conidia generation were respectively 60 and 40 µmol•m −2 •s −1 [11]. Similar light responses have been reported in other A. oryzae strains [12].…”
Section: Introductionsupporting
confidence: 83%
“…A strain of Aspergillus oryzae that is safe to use and widely used in the brewing [1,2], enzyme [3,4], and waste treatment [5,6] industries is photoresponsive to different light wavelengths and intensities [7][8][9][10]. Our earlier investigation demonstrated that A. oryzae GDMCC 3.31 is more sensitive to CBL (475 nm) than to red light (630 nm) [11]. CBL, whose intensity is higher than the threshold, significantly inhibited A. oryzae GDMCC 3.31.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…These methods include colour filters with defined transmission spectra placed on the Petri dish lid [ 5 , 25 , 33 ], modified incubators with specific lamps or custom-made devices (e.g., [ 2 , 4 ]), and commercial growth cabinets with integrated illumination (e.g., [ 4 , 34 ]). Only one recent paper describes for the first time a targeted light incubation from below, thus enabling the LED light source to be replaced more easily [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…These methods include colour lters with de ned transmission spectra placed on the Petri dish lid [5,25,33], modi ed incubators with speci c lamps or custom-made devices (e.g., [2,4]), and commercial growth cabinets with integrated illumination (e.g., [4,34]). Only one recent paper describes for the rst time a targeted light incubation from below, thus enabling the LED light source to be replaced more easily [35].…”
Section: Introductionmentioning
confidence: 99%